Celecoxib and rofecoxib have different effects on small intestinal ischemia/reperfusion injury in rats - László, Szilvia B.; Hutka, Barbara; Tóth, András S.; Hegyes, Tamás; Demeter, Zsuzsanna O.; Haghighi, Arezoo; Wachtl, Gerda; Kelemen, Ágnes; Jakab, Anna; Gyires, Klára; Zádori, Zoltán S. (Frontiers in Pharmacology, 2024)
Introduction. Intestinal ischemia/reperfusion (I/R) injury is associated with high mortality and there is an unmet need for novel therapies. The intestinal expression of cyclooxygenase-2 (COX-2) increases rapidly after mesenteric I/R, but it is still a question of debate whether selective COX-2 inhibitors can mitigate I/R-induced gut injury. Here we aimed to compare the effect of celecoxib and rofecoxib, two selective COX-2 inhibitors, on intestinal I/R-induced injury in rats. Methods. Wistar rats were treated with celecoxib (10 and 100 mg/kg), rofecoxib (5 and 50 mg/kg), or vehicle for 8 days via gavage and then were subjected to sham operation or mesenteric I/R. Small intestinal inflammation and tissue damage were assessed by histology and quantification of inflammatory and tight junction proteins. The intestinal activity of COX enzymes was determined by a COX activity assay. Results. The higher dose of celecoxib reduced the I/R-associated increase in inflammatory mediators (myeloperoxidase, pentraxin 3, COX-2, interleukin-1β) and loss of tight junction proteins (claudin-1, occludin), whereas the lower dose of celecoxib was only marginally effective. However, even high-dose celecoxib failed to prevent the histological injury of the mucosa. In contrast to celecoxib, rofecoxib did not affect intestinal inflammation and injury at any of the tested doses. Neither celecoxib nor rofecoxib affected the I/R-induced changes of HO-1 and PPAR-γ, known off-targets of COX-inhibitors, but celecoxib increased the I/R-induced elevation of Bax/Bcl-2, a marker of apoptosis, whereas rofecoxib reduced the elevation of phospho-Akt. Importantly, high-dose celecoxib, but not rofecoxib, has already reduced intestinal COX-1 activity. Conclusions. Our study provides evidence for the higher anti-inflammatory efficacy of celecoxib compared to rofecoxib in mesenteric I/R injury, which is likely due to its lower selectivity for COX-2. However, even high-dose celecoxib was unable to reduce the mucosal damage. Our results suggest that selective COX-2 inhibitors have only limited therapeutic value in intestinal I/R injury.